Mutilated Veterans: The Heroic Representation of Disability in Italian Children’s Literature - Silvia Pacelli (Educació i Història: Revista d'Història de l'Educació, 2025)
This paper highlights the significant change in the representation of disability in children’s literature with the advent of World War I and fascism in Italy in order to clarify the use of disabled veteran characters for ideological purposes. During wartime, in Italy, there is a substantial increase in the production of books with historical and war themes as well as biographies emphasizing the heroism and sacrifice of those who defended their nation. Many works of children’s literature implicitly aim to educate future recruits in the values of sacrifice for the homeland, and they prematurely militarise childhood and children’s play. The Italian entry into the war leads to a major turning point in the representation of disability in children's books: the huge number of war invalids drives an unprecedented revaluation of the image of physical disabilities, mutilated veterans become a legitimate social issue, and their representation gains a new public dignity because their bodies bear the marks of their patriotism and valiant sacrifice. However, the representation of disabled veterans in children’s books is typically one-dimensional and serves ideological purposes.